Phtochemical Compounds Test of Lemongrass Extract (Cymbopogon Citratus) Using Maceration Method - Alfiyanti, Windi Indra; Ferdyanti, Anggun Putri; Rohman, Ahmad Fatur; Agustina, Eva; Putnamasari, Risa; Kusumawati, Estri (International Conference on Sustainable Health Promotion, 2023)
Lemongrass (Cymbopogon citratus) is a spice plant that contains active compounds that can be used as a cooking spice and medicine. The purpose of this study was to determine the phytochemical compounds in lemongrass a qualitatively and to determine the levels of phenolic compounds quantitatively. The method used to extract the structure of compounds in lemongrass plants is maceration using ethanol as a solvent. Phytochemical test qualitatively by looking at physical and chemical changes. Quantitative phytochemical tests determine the levels of phenolic compounds using the UV-VIS Spectrophotometer instrument and identification of bonds between compounds using the FTIR (Fourier Transform Infra Red) instrument. The results of the phytochemical test qualitatively contained alkaloids, flavonoids, and triterpenoids. The results of the quantitative phytochemical test in the extract contained a total phenolic content of 6.379 mg/g. Based on the identification of phenolic compounds using FTIR, there are wave peaks around 3400-3600 cm-1 indicating the presence of O-H bonds in the phenolic hydroxyl groups. In addition, the presence of a peak wave number around 1600-1700 cm-1 indicates the presence of a C=O bond in the ketone or aldehyde group.